2017
DOI: 10.5301/jbm.5000238
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms of TLR2 and TLR3 in HBV Clearance and HBV-Related Hepatocellular Carcinoma in a Chinese Male Population

Abstract: This study revealed that TLR2 rs3804100 and TLR3 rs3775291 polymorphisms may be protective factors for HBV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Our observation regarding the association of TLR3 risk variants with HBsAg SC contradicts findings of previous studies 16 , 22 24 . Sa et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our observation regarding the association of TLR3 risk variants with HBsAg SC contradicts findings of previous studies 16 , 22 24 . Sa et al .…”
Section: Discussioncontrasting
confidence: 99%
“… 27 and Chen et al . 22 in Asian patients. Their studies suggest that the TLR3 SNP rs3775291 is a novel risk factor for HBV-related HCC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, 22 articles were included in this study, including five articles on TLR3 rs3775291 polymorphism and the risk of HBV [10][11][12][13][14] and 17 articles on IL-10 rs1800871 and susceptibility to HBV [16][17][18][19][25][26][27][28][29][30][31][32][33][34][35][36][37]. The detailed literature screening process was shown in Figure 1.…”
Section: Results Of Literature Retrievalmentioning
confidence: 99%
“…Rong et al [11] and Fischer et al [12] reported that allele T at the TLR3 rs3775291 loci increased the risk of HBV infection. However, other studies [13,14] suggested that its allele T was not related to the risk of HBV infection. IL-10, an important Th2 cytokine, plays an essential regulatory role in the immune process of HBV infection.…”
Section: Introductionmentioning
confidence: 94%
“…The RIG-I like receptors consist of three members, including DDX58/RIG-I (retinoic acid-inducible gene I), IFIH1/MDA-5 (melanoma differentiation-associated gene 5), and DHX58/LGP-2 (laboratory of genetics and physiology 2).They can sense viral RNA and induce powerful antiviral and pro-inflammatory gene expressions [ 32 34 ]. Among various Toll-like receptors (TLRs), TLR2 and TLR3 play a significant role in the modulation of virus-mediated innate immune response and trigger anti-viral signal pathways [ 36 39 ]. However, the mechanism and role of RNA editing changes during viral infection are yet to be completely elucidated.…”
Section: Introductionmentioning
confidence: 99%